DOUBLE FILLET WELDING OF CARBON STEEL T-JOINT BY DOUBLE CHANNEL SHIELDING GAS METAL ARC WELDING METHOD USING METAL CORED WIRE - Mert, T.; Gultekin, N.; Karaaslan, A. (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST METALL & MATER SCI PAS, 2017)
Low carbon steel material and T-joints are frequently used in ship building and steel constructions. Advantages such as high deposition rates, high quality and smooth weld metals and easy automation make cored wires preferable in these industries. In this study, low carbon steel materials with web and flange thicknesses of 6 mm, 8 mm and 10 mm were welded with conventional GMAW and double channel shielding gas metal arc welding (DMAG) method to form double fillet T-joints using metal cored wire. The difference between these two methods were characterized by measurements of mean welding parameters, Vickers hardness profiles, weld bead and HAZ geometry of the joints and thermal camera temperature measurements. When weld bead and HAZ geometries are focused, it was seen filler metal molten area increased and base metal molten area decreased in DMAG of low carbon steel. When compared with traditional GMAW, finer and acicular structures in weld metal and more homogenous and smaller grains in HAZ are obtained with double channel shielding gas metal arc welding.
Keywords: Double channel torch; low carbon steel; metal cored wire; T-joint; microstructure; STAINLESS-STEEL; Metallurgy & Metallurgical Engineering